Analyzing Police Communication Strategies for Preventing Teenage Drug Abuse in Simpang Kanan Subdistrict, Rokan Hilir Regency - Jollyta, Jollyta; Denny, Denny; Simbolon, Romasinta; Panjaitan, Firta Sari (Law and Economics, 2022)
This research delves into the efficacy of police communication strategies in combating drug abuse among teenagers in Simpang Kanan Subdistrict, situated within the Rokan Hilir Regency of Indonesia. Utilizing a mixed-methods approach, the study navigates the intricate interplay of cultural dynamics, community engagement, and the effectiveness of varied communication channels employed by law enforcement agencies. Quantitative analysis unveils statistical trends in drug abuse prevalence among teenagers, shedding light on the impact of specific communication strategies. Concurrently, qualitative exploration delves into perceptions, experiences, and stakeholder feedback, offering depth to the understanding of the multifaceted issue. Findings underscore the strengths of community engagement initiatives and diverse communication channels, showcasing heightened awareness and positive behavioral shifts among teenagers. Yet, limitations such as data constraints, sampling intricacies, and resource limitations temper the comprehensiveness of the analysis. The implications drawn from this research advocate for tailored, culturally sensitive approaches, community-driven interventions, and continuous evaluation mechanisms in future policy changes. These insights transcend regional boundaries, offering a framework adaptable to analogous contexts worldwide. This research serves as a beacon, illuminating pathways toward combating teenage drug abuse.